(untitled) (Research, Society and Development, 2020)
The objective of this study was to investigate the production and commercialization systems, focusing on the role of short food chains in the income formation of farmers in the northwestern Region of Rio Grande do Sul. These pieces of data were collected between January and March 2018, by means of a structured road map and an Agrarian Systems approach was used to economically estimate the systems of five farmers. The results show that incomes derived from the short supply food chains represent approximately 60% in two production units; more than 75% in two others; in only one of them the income is approximately 46% of the total income. This configuration in the income formation demonstrates the importance of this type of market in the socioeconomic reproduction of the analyzed farmers, especially when observing the income composition in a stratified form. The forms of insertion in the local markets were motivated by different expectations such as: increased income, diversification of economic activities or even traditional and cultural aspects of the region.